Sustainability reporting practices in SMEs. A systematic study and future avenues - Cicchini, Daniela; Cotana, Maria Luisa; Filocamo, Maria Rita; Galeotti, Rubina Michela (Piccola Impresa / Small Business, 2024)
Purpose. The aim of the research is to analyse the current state of the art of the debate on sustainability reporting practices tailored specifically for SMEs. Design/methodology/approach. We applied a systematic literature analysis using Scopus and Web of Science as leading databases in searching studies. The initial sample was composed of 85 articles. After the screening process, we selected a final sample of 33 papers that we investigated under the lens of Alvesson and Deetz (2000) providing insights, criticisms and transformative redefinition. Findings. We retrieved three research areas: (i) IR and SMEs; (ii) CSR reporting and SMEs; (iii) SDGs reporting, circular economy and SMEs. Our results highlight the pros and cons of the adoption of these sustainability reporting models by SMEs, offering critical issues and future avenues. Practical and Social Implications. This study provides both theoretical and practical implications. The theoretical implications refer to its contribution to advancing the research field by providing valuable insights for future investigations. From a practical standpoint, this study can serve as a catalyst for SME managers to embrace sustainability reporting models. Originality of the study. The originality of this study derives from the first-time to draft what are sustainability reporting practices in SMEs. This paper is directed to academic and practical communities.